2021
DOI: 10.1177/1532440020945285
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Chief Justices by Peer Vote

Abstract: What characteristics do state supreme court justices prioritize when choosing leaders? At the federal level, collegial court leaders are appointed or rotated by seniority. A plurality of states permit peer-vote selection, but the consequences of employing this mechanism are not well known. We develop a theory of chief justice selection emphasizing experience, bias, and politics. Leveraging within-contest variation and more than a half century’s worth of original contest data, we find that chief justice peer vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Langer et al (2003) found that ideologically extreme judges are less likely to be elected as chief justice by their peers. More recent scholarship by Fife, Goelzhauser, and Loertscher (2021) concludes that ideological tendencies are less influential than the rate at which a justice dissents from the court's decisions.…”
Section: Prior Research On Chief Justice Selection Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Langer et al (2003) found that ideologically extreme judges are less likely to be elected as chief justice by their peers. More recent scholarship by Fife, Goelzhauser, and Loertscher (2021) concludes that ideological tendencies are less influential than the rate at which a justice dissents from the court's decisions.…”
Section: Prior Research On Chief Justice Selection Rulesmentioning
confidence: 99%
“…The current supreme court justices also ought to be informed and sophisticated when picking a chief justice (Fife, Goelzhauser, and Loertscher 2021;Langer et al 2003). They have already worked alongside the relevant candidates in a small group setting and likely formed opinions about their strengths and weaknesses.…”
Section: Prior Research On Chief Justice Selection Rulesmentioning
confidence: 99%